2004
DOI: 10.1071/ar03262
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site evaluation on acid soils of a Phalaris aquatica × P. arundinacea × P. aquatica backcross population bred for acid soil tolerance

Abstract: Half-sib families in the AT98 Phalaris aquatica × P. arundinacea × P. aquatica backcross population bred for acid soil tolerance were compared for establishment, persistence, and yield with phalaris (P. aquatica L.) controls and cocksfoot (Dactylis glomerata L. cv. Porto) at 4 sites in south-eastern Australia with the aim of selecting the parents of a new cultivar. The sites had strongly acid soils but differed in parent material, pH profile, soil fertility, and suitability for phalaris. Establishment by AT98 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…While Sirosa-phalaris is sensitive to acidity, its total root length in the unamended soils was often similar to that of AT-phalaris. This cultivar displays vigorous growth in the field and this may explain why acid-soil resistant lines of phalaris do not always display a clear advantage over Sirosa-phalaris at acid field sites (Culvenor et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While Sirosa-phalaris is sensitive to acidity, its total root length in the unamended soils was often similar to that of AT-phalaris. This cultivar displays vigorous growth in the field and this may explain why acid-soil resistant lines of phalaris do not always display a clear advantage over Sirosa-phalaris at acid field sites (Culvenor et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The bar shows least significant difference value (P=0.05) for the interaction of soil amendment x species (LSD=0.0033, Ferrosol, 0.0062, Kandosol topsoil, 0.0058, Kandosol subsoil). Rhizosheath refers to soil held to the root system when the root system has been excavated from soil species differences in Al-resistance for AT-and Sirosaphalaris (Culvenor et al 2004). However, rhizosheaths of both genotypes were adversely affected by soil acidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2006; Botwright Acuna, Pasuquin & Wade 2007; Blum 2009). At an acid‐soil field site, Culvenor et al . (2004) found that an acid‐soil sensitive cultivar of phalaris achieved equivalent plant establishment prior to the summer drought compared with that of an acid‐soil resistant line.…”
Section: Discussionmentioning
confidence: 99%